Teori Emanasi Filosof Muslim dan Relevansinya dengan Sains Modern - Barsihannor Barsihannor (AL-Fikr, 2010)
Discourse on whether this universe was created from nothing (creatio ex nihilo) or from already existing material, has been a polemic along with the history of human civilization. This article is trying to present the process of creating the universe based on modern science and from the perspective of Muslim philosophers, particularly on emanation theory. According to Muslim philosophers, this universe was created from prime matter through the process of divine ta’aqqul, which later created reasons to manage materials of the universe. Emanation theory presents that God, the most sacred, has no direct relation to matters. God merely delegates to His reasons (emanation) to run the universe mechanism.